Those kids from fawn creek eaudiobook - Kelly, Erin Entrada (Greenwillow Books, 2022)
"A powerful and thought-provoking story." —Shelf Awareness (starred review) "An emotionally resonant story about authenticity and belonging." —Kirkus Reviews (starred review) "A raw, real exploration of belonging that's also sweetly hopeful." —Publishers Weekly (starred review) Every day in Fawn Creek, Louisiana, is exactly the same—until Orchid Mason arrives. From Erin Entrada Kelly, the winner of the Newbery Medal for Hello, Universe and a Newbery Honor for We Dream of Space, this contemporary school story set in small-town Louisiana is about friendship, family, deception, and being true to yourself and your dreams. There are twelve kids in the seventh grade at Fawn Creek Middle School. They've been together all their lives. And in this small factory town where everyone knows everything about everyone, that's not necessarily a great thing. There are thirteen desks in the seventh-grade classroom. That's because Renni Dean's father got a promotion, and the family moved to Grand Saintlodge, the nearest big town. Renni's desk is empty, but Renni still knows their secrets; is still pulling their strings. When Orchid Mason arrives and slips gracefully into Renni's chair, the other seventh graders don't know what to think. Orchid—who was born in New York City but just moved to Fawn Creek from Paris—seems to float. Her dress skims the floor. She's wearing a flower behind her ear. Fawn Creek Middle might be small, but it has its tightly knit groups—the self-proclaimed "God Squad," the jocks, the outsiders—just like anyplace else. Who will claim Orchid Mason? Who will save Orchid Mason? Or will Orchid Mason save them? Newbery Medal and Newbery Honor winner Erin Entrada Kelly explores complex themes centered on family, friendships, and staying true to yourself. Those Kids from Fawn Creek will enchant fans of Rebecca Stead, Jerry Spinelli, and Kate DiCamillo.